Science Teaching in Islamic Civilization: an Analysis of Ibn Khaldun's Muqaddimah - Bahrum Subagiya; Endin Mujahidin (JURNAL AT-TURAS, 2023)
Islamic civilization has contributed significantly to the advancement of world science. This statement is revealed from the many Muslim scientists who contributed significantly to various scientific discoveries in every field, which inspired European scientists. In addition, the science developed also has its uniqueness and Islamic characteristics. The number of Muslim scientists and the development of science in the Islamic world raises a question of how science teaching is done in the Islamic world and what kind of science is taught. This research aims to reveal the uniqueness of science teaching applied in the history of Islamic civilization by analyzing the book Muqaddimah by Ibn Khaldun. This research is descriptive qualitative research with a literature review approach. The results found that the uniqueness of science teaching in Islamic civilization is centered on faith in Allah, not denying and involving the role of God in science teaching. The method applied in teaching science is done in stages (at-tadrij), repeating lessons (at-takrir) and developing them with experience and experimentation (at-tajribi). The science teaching strategy applied is establishing an authoritative teacher, understanding the learner's thinking and readiness, emphasizing teaching based on objectives, and simplifying instruction.